Modification of human high density lipoprotein (HDL3) with tetranitromethane and the effect on its binding to isolated rat liver plasma membranes. - G K Chacko (Journal of Lipid Research, 1985)
Apolipoprotein E-free high density lipoproteins (HDL) bind to various cells and cell membrane preparations, with properties typical of ligand-receptor interactions. In order to further characterize the binding sites and to investigate the functional role of binding, a chemically modified HDL without the specific binding properties would be highly desirable. We have reacted human HDL3 with tetranitromethane, a relatively specific nitrating reagent for tyrosine residues, in 50 mM Tris HCL buffer, pH 8.0, and at a reagent concentration 10 times the molar excess of tyrosine residues. The resulting nitrated HDL3 completely lost its ability to bind to high affinity saturable binding sites of rat liver plasma membranes, as determined by competitive binding with 125I-labeled HDL3, and also by direct binding assays using 125I-labeled nitrated HDL3. Although nitrated HDL3 did not bind to the high affinity saturable binding sites, it bound to the membranes, but the binding was not saturable, and was not competed for by unlabeled nitrated HDL3. On agarose gel electrophoresis, pH 8.6, the nitrated HDL3 moved ahead of the control HDL3, indicating an increase in negative charges in the molecule. No difference in size was noted in the nitrated HDL3 when analyzed either by negative stain electron microscopy or by gel filtration chromatography. Spectroscopic analysis of the nitrated HDL3 at pH 8.0 revealed a prominent absorption with maximum at around 360 nm, but none in the region expected for nitrotyrosine residues. At pH 10.0, however, the nitrated HDL3 showed an absorption band with a maximum at around 440 nm, possibly related to nitrotyrosine residues. Nitrotyrosine was detected in the nitrated HDL3 on amino acid analysis. Comparison of the amino acid analysis of the nitrated HDL3 and control HDL3 showed no difference in composition of any of the amino acids except tyrosine; tyrosine content was reduced more than 90% in the nitrated HDL3. SDS-polyacrylamide gel electrophoresis analysis of apoproteins of nitrated HDL3 revealed changes in apolipoprotein profile. Bands corresponding to the apolipoproteins of the starting HDL3 almost disappeared and a series of new bands appeared at the high molecular weight region of the gel, indicating extensive cross-linking of apolipoproteins during the reaction. In addition, a substantial amount of phospholipids and cholesteryl esters, but not unesterified cholesterol, was found covalently linked, possibly through the unsaturated centers of the fatty acid chains, to apolipoproteins.(ABSTRACT TRUNCATED AT 400 WORDS)